Mitophagy as an active regulator of cardiac metabolic reprogramming - Li Gai; Yan Li; Chen Yang; Mengya Wang (Frontiers in Cardiovascular Medicine, 2026)
Mitophagy is increasingly recognized as a context-dependent regulator of cardiac metabolic adaptation rather than solely as a disposal pathway for damaged mitochondria. By coupling mitochondrial turnover to substrate selection, redox control, and inflammatory signaling, mitophagy can influence fatty acid oxidation (FAO), glycolysis, and oxidative phosphorylation (OXPHOS) in cardiomyocytes, vascular endothelial cells, and immune cells. In this review, the term Mitophagy–Metabolic Rewiring Axis (MMRA) is used as an integrative conceptual framework—not as a newly discovered pathway or theory—to organize evidence for bidirectional interactions between mitophagy and metabolic remodeling. The framework comprises stress inputs, mitophagy machinery and flux, metabolic outputs, and cell- or disease-level consequences, while emphasizing that the biological effect of mitophagy depends on cell type, disease stage, and duration of activation. We critically assess the AMP-activated protein kinase (AMPK)–UNC-51-like kinase 1 (ULK1), sirtuin 3 (SIRT3)–peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC-1 α ), PTEN-induced kinase 1 (PINK1)–Parkin E3 ubiquitin ligase, and hypoxia-inducible factor 1-alpha (HIF-1 α )–BCL2-interacting protein 3 (BNIP3)/FUN14 domain-containing 1 (FUNDC1) modules in atherosclerosis, heart failure, and ischemia/reperfusion injury. Pharmacological, substrate-based, and exercise interventions are evaluated with particular attention to the predominantly preclinical evidence base, methodological limitations in measuring mitophagy flux, and the need for validated human biomarkers. Multi-omics and spatial approaches may improve mechanistic resolution, but clinical translation will require prospective studies that link target engagement to metabolic and cardiovascular outcomes.